ANALISIS KONTRIBUSI PAJAK REKLAME DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH DI KABUPATEN SIDOARJO TAHUN 2011-2013 - WIDOWATI, SANTHYA (Jurnal Akuntansi AKUNESA, 2014)
Regional of embodiments development and regional financial governance, Law No. 28 of 2009 on Local Taxes and Levies are one source of local revenue. Study uses quantitative methods. This study to determine the contribution of Advertisement Tax Revenue in Developing Regions to like this how much acceptance of advertisement tax revenue in this sector annually bigger or getting down to the level of contributions. The results of the analysis and discussion on the development of advertisement tax beginning in 2011 the target of 1.905.993.882.859,38, 2.005.191.397.714,27 realizable value percentage 105.20%. Whereas in 2012 the target 2284511936806.00, 2.317.444.096.384,41 realizable value, and the percentage of 101.44%. If in 2013 the target of increased 2.644.581.299.007,00, 2.695.270.157.664,95 realizable value, and the percentage of 101.95%. For advertisement tax contribution of the year 2011 amounted to 1.68%, 1.28% in 2012, 1.03% in 2013 due to decreased and the proportion of the original income Sidoarjo lack of consumer interest to put the advertisement tax.Keyword: Contribution Advertisement tax, District Own Local Revenue